Food for life : the new science of eating well - Spector, T. D. (Timothy David) (Jonathan Cape, 2022)
A comprehensive guide to the new science of nutrition. Food is our greatest ally for good health, but the question of what to eat has never seemed so complicated.Spector creates a unique, thorough, evidence-based guide to the real science of eating. Moving away from misleading notions of calories or nutritional breakdowns, Food for Life empowers us to make our own food choices based on a deeper understanding of the true benefits and harms that come from our daily transactions with the foods around us. Combining cutting-edge research with a personal insights, and taking a wide angle lens on everything from environmental impact and food fraud to allergies and deceptive labelling, Spector takes a deep dive into each food type. He also includes easy-to-implement action points and useful tables as practical tools in our everyday food decisions.